Reconsidering the ethics of compulsive treatment in light of clinical psychiatry : a selective review of literature - Madeira, Luís Duarte; Santos, Jorge Costa (F1000Research, 2022)
The ethics of compulsive treatment (CT) is a medical, social and legal discussion that reemerged after the ratification by 181 countries of the 2007 United Nations Convention on the Rights of Persons with Disabilities (UN-CRPD). The optional protocol of the UN-CRPD was ratified by 86 countries aiming to promote, protect and ensure the full and equal enjoyment of all human rights. It also determined the need to review mental health laws as under this light treatment of persons with disabilities, particularly those with mental disorders, cannot accept the use of CT. This selective review of literature aims to clarify inputs from clinical psychiatry adding evidence to the multi-disciplinary discussion. It provides contradictory evidence on how patients experience CT and its impact on their mental health and treatment programs, also which are main reasons for the use of CT and what efforts in psychiatry have been made to reduce, replace and refine it.
Keywords: involuntary treatment; ethics; persons with disabilities; human rights